Pengaruh Profitabilitas, Likuiditas Dan Leverage Terhadap Harga Saham Pada Perusahaan Sub Sektor Food And Beverage Yang Terdaftar Di BEI Periode 2017-2019 - Indah Ramadhani; Ronny Malavia Mardani; Nurhidayah Nurhidayah (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this study was to determine the effect of profitability, liquidity and leverage on stock prices in the food and beverage sub-sector companies listed on the IDX for the 2017-2019 period. The population used in this study is a manufacturing industry company in the food and beverage sub-sector with a purposive sampling technique, namely the 2017-2019 period. This research method uses multiple linear regression analysis.The results of this study indicate that (1) Profitability (Return on Assets) has a significant positive effect on stock prices. (2) Liquidity (Current Ratio) has a negative and insignificant effect on stock prices. (3) Leverage (Debt to Equity Ratio) has a negative and insignificant effect on stock prices. Keywords: profitability (Return On Asset), liquidity (Current Ratio), leverage (Debt to Equity Ratio, stock price